The value of information in a cooperative environment - Galdeano, Patricia; Oviedo, Jorge; Quintas, Luis Guillermo (Estudios de Economía, 2016)
In this paper we analyze the value of the information in a cooperative game. There is a player, the innovator, having a know how or relevant information which is not useful for himself but it can be sold to some potential buyers. The n potential users of the information are involved in a market having all them the same characteristics. The expected utility of each of them can be improved by obtaining the information. The whole situation is modeled as a (n + 1)–person game. The Shapley Value is the cooperative solution studied. We deal with a game in characteristic form function, where this function can be non-superaditive. Supearditivity have been a usual assumption in cooperative games, but we show that under a weak version of superaditivity it is still possible to use the Shapley Value as a cooperative solution. We give conditions for the weak superaditivity and study the implications of those conditions on the resulting market. We also compare the Shapley Value with the outcomes obtained in a noncooperative approach by Quintas (1995). Finally we arrive to the conclusion that the innovator prefers the noncooperative outcome and the users prefer the cooperative outcomes.